Burnout syndrome in studennts of accounting courses of a public university - Almeida, Ricardo Santana de (2023)
This study aims to analyze the relationship and differences between the subdimensions of the Burnout syndrome (exhaustion, cynicism and personal fulfillment) with sociodemographic variables (gender, age, income and financial problem) and variables of academic experience (campus, period enrolled, in the CBT phase) in students of two undergraduate courses in Accounting. The research was conducted with the academics of the Accounting Sciences course in a multicampus university in the south of the country. Correlation analyses and mean difference test (Kruskal-Wallis mean ranks) were used to verify, respectively, possible relationships and mean differences between Burnout and its subdimensions. As main results, it was found that two variables correlated with Burnout: income and CBT. Investigating this relationship by subdimensions of Burnout, we have that CBT and financial problems are related to the subdimension "exhaustion"; period enrolled with "cynicism"; campuses and enrollment related to "personal fulfillment." When ascertaining the location of the differences, the following stand out: in "exhaustion": gender, financial problems and CBT. "Cynicism": Differences increase as the course progresses and decrease "personal fulfillment," varying by campus. The findings allowed the identification of relationships and differences, in addition to indicating future investigations on factors generating the syndrome in the delimited courses.